MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) SISWA KELAS VA SDN 006 KUBANG JAYA KECAMATAN SIAK HULU - Marskal Ujang (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The problem of this research is of low grade student learning outcomes VA SDN 006 Kubang Jaya Kecamatan Siak Hulu. This learning problem addressed by implementing cooperative learning model numbered heads together (NHT) with the formulation of the problem: Does the implementation of cooperative learning model Numbered Heads Together (NHT) can improve learning outcomes IPS graders of VA SDN 006 Kubang Jaya Kecamatan Siak Hulu? The purpose of this research is to improve learning outcomes IPS graders of VA SDN 006 Kubang Jaya Kecamatan Siak Hulu by means of the application of cooperative learning model numbered heads together (NHT). This research is a class act performed two cycles, the subject of this research is class VA with the number of 33 students, the study was conducted with four stages: planning, implementation, observation stage, and the stage of reflection. The study states that the results of social studies students has increased. This is evidenced by the results of the first cycle of learning has increased compared to conventional learning, the average value of learning outcomes prasiklus is 50.90, the first cycle average student learning outcomes is 70.00, the second cycle increased again to 77.20, In addition completeness of students has increased in prasiklus is 8 students (25.00%), in the first cycle is 21 students (65.60%), and the second cycle increased to 29 students (90.60%). Based on the results of this study concluded that the implementation of cooperative learning model type numbered heads together (NHT) can improve learning outcomes IPS graders of VA SDN 006 Kubang Jaya Kecamatan Siak Hulu.